Is transcranial direct current stimulation (tDCS) effective to improve cognition and functionality after severe traumatic brain injury? A perspective article and hypothesis - Cordeiro, Bárbara Naeme de Lima; Kuster, Elizângela; Thibaut, Aurore; Rodrigues Nascimento, Lucas; Gonçalves, Jessica Vaz; Arêas, Guilherme Peixoto Tinoco; Paiva, Wellingson Silva; Arêas, Fernando Zanela da Silva (Frontiers in Human Neuroscience, 2023)
Severe traumatic brain injury (sTBI) is an important cause of disability and mortality and affects people of all ages. Current scientific evidence indicates that motor dysfunction and cognitive impairment are the main limiting factors in patients with sTBI. Transcranial direct current stimulation (tDCS) seems to be a good therapeutic option, but when it comes to patients with sTBI, the results are inconclusive, and some protocols have not yet been tested. In addition, there is still a lack of information on tDCS-related physiological mechanisms, especially during the acute phase. In the present study, based on current evidence on tDCS mechanisms of action, we hypothesized that performing tDCS sessions in individuals with sTBI, especially in the acute and subacute phases, Neuromodulation after severe traumatic brain injury: Review and hypothesis 2 together with conventional therapy sessions, could improve cognition and motor function in this population. This hypothesis presents a new possibility for treating sTBI, seeking to elucidate the extent to which early tDCS may affect long-term clinical outcomes.